Prevalence of Vitamin D Deficiency in Pediatric Patients with Sickle Cell Disease: A Systematic Review - De Moraes-Ferrari, G (Elsevier B.V., 2025)
Hypovitaminosis D is significantly more prevalent in sickle cell disease (SCD) compared to healthy control patients. The absence of adequate vitamin D levels in patients with a chronic inflammatory condition may exacerbate inflammation, worsening the disease. Therefore, a systematic review was conducted analyzing articles from the Medline database of the National Institute of Medicine between April 2023 and November 2023. Inclusion criteria were observational studies in pediatric populations up to 20 years old, published in English. Intervention studies, clinical trials, abstracts, and reviews were excluded. The final number of selected articles was 18 of 85 listed. The overall frequency of vitamin D deficiency in the pediatric age group with SCD was 50.49 % (569 out of 1127), considering 20 ng/mL (50 nmol/L) as the cutoff for deficiency, the most commonly used reference level for vitamin D deficiency in the listed studies. The prevalence of vitamin D deficiency in this population appeared to be higher when compared to children and adolescents without SCD. Our review concluded that vitamin D deficiency is prevalent in the pediatric population with SCD, but future studies should confirm the implications of this finding. © 2025 Pediatric Hematology Oncology Chapter of Indian Academy of Pediatrics